Anaerobic membrane bioreactor effluent reuse: a review of microbial safety concerns - Harb, Moustapha (2017)
Broad and increasing interest in sustainable wastewater treatment has led a paradigm shift towards more efficient means of treatment system operation. A key aspect of improving overall sustainability is the potential for direct wastewater effluent reuse. Anaerobic membrane bioreactors (AnMBRs) have been identified as an attractive option for producing high quality and nutrient-rich effluents during the treatment of municipal wastewaters. The introduction of direct effluent reuse does, however, raise several safety concerns related to its application. Among those concerns are the microbial threats associated with pathogenic bacteria as well as the emerging issues associated with antibiotic-resistant bacteria and the potential for proliferation of antibiotic resistance genes. Although there is substantial research evaluating these topics from the perspectives of anaerobic digestion and membrane bioreactors separately, little is known regarding how AnMBR systems can contribute to pathogen and antibiotic resistance removal and propagation in wastewater effluents. The aim of this review is to provide a current assessment of existing literature on anaerobic and membrane-based treatment systems as they relate to these microbial safety issues and utilize this assessment to identify areas of potential future research to evaluate the suitability of AnMBRs for direct effluent reuse.